INVESTIGATING AI TOOLS USAGE IN ENGLISH FOR PRESENTATION: A STUDY OF STUDENTS AT TWO PRIVATE HIGHER EDUCATIONAL INSTITUTIONS IN BANDUNG - Arni Sukmiarni; Lenny Kristianti (Jurnal Sastra - Studi Ilmiah Sastra, 2024)
The increasing adoption of artificial intelligence (AI) in education is transforming the methods through which students engage with English learning. This study seeks to explore the potential of AI in supporting university students' English language Learning. By examining current AI usage, the research aims to assess students' familiarity with AI tools and the extent to which they integrate these tools into their English learning practices. Participants in the study are enrolled in the mandatory online English III course, "English for Presentation," at two private higher educational institutions in Bandung, Indonesia, reflecting a range of English proficiency levels among them. Data collection involved administering questionnaires to participants at the end of the odd term in the academic year 2023-2024. The findings indicate that a significant majority of participants are aware of AI tools, with Google Translate emerging as the most frequently used tool for language learning assistance. However, the potential of other AI tools to assist English language learning for presentations has not been fully explored. Respondents are now more aware of how to use AI tools effectively: using precise prompts, verifying AI results, not relying solely on AI, continuing manual research, and understanding that AI can help with ideas and presentations but requires verification, moderation and ethical use of AI are essential. Instructors are recommended to provide guidance and facilitate the exploration of AI tools to effectively integrate them into students’ learning.